Synthesis and DFT Calculations of Novel Vanillin-Chalcones and Their 3-Aryl-5-(4-(2-(dimethylamino)-ethoxy)-3-methoxyphenyl)-4,5-dihydro-1H-pyrazole-1-carbaldehyde Derivatives as Antifungal Agents - Illicachi, Luis Alberto (Molecules, 2017)
Novel (E)-1-(aryl)-3-(4-(2-(dimethylamino)ethoxy)-3-methoxyphenyl) prop-2-en-1-ones 4 were synthesized by a Claisen-Schmidt reaction of 4-(2-(dimethylamino)ethoxy)-3-methoxy-benzaldehyde (2) with several acetophenone derivatives 3. Subsequently, cyclocondensation reactions of chalcones 4 with hydrazine hydrate afforded the new racemic 3-aryl-5-(4-(2-(dimethylamino)ethoxy)-3-methoxyphenyl)-4,5-dihydro-1H-pyrazole-1-carbaldehydes 5 when the reaction was carried out in formic acid. The antifungal activity of both series of compounds against eight fungal species was determined. In general, chalcone derivatives 4 showed better activities than pyrazolines 5 against all tested fungi. None of the compounds 4a–g and 5a–g showed activity against the three Aspergillus spp. In contrast, most of the compounds 4 showed moderate to high activities against three dermatophytes (MICs 31.25–62.5 µg/mL), being 4a followed by 4c the most active structures. Interestingly, 4a and 4c possess fungicidal rather than fungistatic activities, with MFC values between 31.25 and 62.5 μg/mL. The comparison of the percentages of inhibition of C. neoformans by the most active compounds 4, allowed us to know the role played by the different substituents of the chalcones’ A-ring. Also the most anti-cryptococcal compounds 4a–c and 4g, were tested in a second panel of five clinical C. neoformans strains in order to have an overview of their inhibition capacity not only of standardized but also of clinical C. neoformans strains. DFT calculations showed that the electrophilicity is the main electronic property to explain the differences in antifungal activities for the synthesized chalcones and pyrazolines compounds. Furthermore, a quantitative reactivity analysis showed that electron-withdrawing substituted chalcones presented the higher electrophilic character and hence, the greater antifungal activities among compounds of series 4.